DNA damage in normally and prematurely aged mice. Issue 3 (24th April 2013) - Maslov, Alexander Y.; Ganapathi, Shireen; Westerhof, Maaike; Quispe‐Tintaya, Wilber; White, Ryan R.; Van Houten, Bennett; Reiling, Erwin; Dollé, Martijn E. T.; van, Harry; Hasty, Paul; Hoeijmakers, Jan H. J.; Vijg, Jan
Summary Steady‐state levels of spontaneous DNA damage, the by‐product of normal metabolism and environmental exposure, are controlled by DNA repair pathways. Incomplete repair or an age‐related increase in damage production and/or decline in repair could lead to an accumulation of DNA damage, increasing mutation rate, affecting transcription, and/or activating programmed cell death or senescence. These consequences of DNA damage metabolism are highly conserved, and the accumulation of lesions in the DNA of the genome could therefore provide a universal cause of aging. An important corollary of this hypothesis is that defects in DNA repair cause both premature aging and accelerated DNA damage accumulation. While the former has been well‐documented, the reliable quantification of the various lesions thought to accumulate in DNA during aging has been a challenge. Here, we quantified inhibition of long‐distance PCR as a measure of DNA damage in liver and brain of both normal and prematurely aging, DNA repair defective mice. The results indicate a marginal, but statistically significant, increase in spontaneous DNA damage with age in normal mouse liver but not in brain. Increased levels of DNA damage were not observed in the DNA repair defective mice. We also show that oxidative lesions do not increase with age. These results indicate that neither normal nor premature aging is accompanied by a dramatic increase in DNA damage. This suggests that factors other than DNA damage per se, for example, cellular responses to DNA damage, are responsible for the aging phenotype in mice.